Stratigraphically controlled silicification in Danian chalk and its implications for reservoir properties, southern Danish Central Graben. (May 2020) - Blinkenberg, Kasper H.; Anderskouv, Kresten; Sheldon, Emma; Bjerrum, Christian J.; Stemmerik, Lars
Abstract: The effect of silica on reservoir quality in chalk is subject to continuing debate. In particular, the stratigraphic variations in silica content within the chalk matrix have not been addressed sufficiently. In this study, a new approach is applied to constrain silica variability in reservoir chalk utilizing hand-held X-ray fluorescence (HH-XRF) on samples from four Maastrichtian–Danian cores from hydrocarbon-producing fields in the southern Danish Central Graben. The results indicate a significant lateral and stratigraphic variability in silica concentrations across the study area; data display a common stratigraphic signature in all wells, however, with maximum silica concentrations and minimum porosities occurring in the lower part of the Danian Ekofisk Formation. Correlation between HH-XRF quantified silica concentrations and biostratigraphic data indicates the synchronous onset of an at least semi-regional silica event during the mid-Danian, nannofossil zones NNTp2F–G to NNTp4A–D, whereas the upper boundary of the peak silica unit is poorly constrained. Generally, stratigraphic trends in silica concentrations appear to be negatively correlated with porosity trends. However, comparison between the HH-XRF quantified silica content and reservoir data (porosity, permeability, estimated pore radius and calculated specific surface area) shows poor correlation indicating that silica content within the Ekofisk reservoir is not the only factor controlling the reservoir quality. Unknown complex diagenetic interactions between calcite, silica and clay probably influence the reservoir properties by promoting calcite cementation in stratigraphically controlled zones, making the Ekofisk reservoir much less predictable than the underlying Maastrichtian Tor Formation. Highlights: A new approach is applied to constrain silica in reservoir chalk using HH-XRF. Silica concentrations across the study area display common stratigraphic signatures. Maximum silica values coincide with minimum porosities in the Ekofisk Formation. Combined silica and biostratigraphy point to a synchronous onset of a silica event. A new subdivision of the Ekofisk Formation based on silica content.